Business Strategies for Improving Sales in Muslim Garment Industry: A Case Study of Convection Work - Saragih, Murniati Arinda; Yafiz, Muhammad; Tarigan, Azhari Akmal (IAIN Manado, 2025)
This study aims to analyze the business development strategies of Royal Konveksi & Production, a Muslim fashion convection enterprise, to improve sales performance in Medan City. This research addresses the gap in understanding how SMEs in the Muslim fashion sector can formulate sustainable strategies amid increasing competition and digital transformation. The study employs a descriptive qualitative method, with data collected through observation, interviews, and documentation of business activities and stakeholder perspectives. SWOT analysis is applied to systematically identify the company’s strengths, weaknesses, opportunities, and threats. Findings reveal that Royal Konveksi’s strengths include high-quality products, affordable pricing, over nine years of operational experience, and strong institutional trust. Weaknesses involve dependence on institutional orders, reliance on certain suppliers, and limited logistics partnerships. Opportunities exist in growing demand for Muslim apparel, supportive government policies, and digitalization trends, whereas threats stem from intense market competition and fluctuating raw material prices. Recommended strategies include optimizing digital marketing, diversifying product lines, expanding retail channels, and enhancing cooperation with suppliers and logistics partners. This study contributes both theoretically and practically by providing a framework for sustainable business development strategies in the Muslim fashion sector, serving as a reference for SMEs and offering insights for academic research on SME growth and strategic management.